The conceptualization model of the visibility of medical knowledge and the increase of its application patterns in the metaverse space based on the Glazer database - Hamid Alaghehband; Zahra Alipour Darvishi; Mohammad Feizi Zangir; Ali Hijiha (Shahid Beheshti University of Medical Sciences, 2024)
Background: The lack of visibility of knowledge in the metaverse is the basis of instability challenges and is a prerequisite for new knowledge management and strategy for virtual organizations. This study was conducted in order to conceptualize the visibility of medical knowledge and increase its application patterns in the metaverse space. Methods: The implementation of the current research is fundamental considering the main goal of the research, which is to conceptualize the visibility of medical knowledge in the metaverse. The statistical population is a collection of experts in the field of Metaverse. To interview the experts used the snowball sampling method, which is a part of non-probability and theoretical sampling. The tool for collecting information was a semi-structured interview checklist regarding the purpose of the study. And the data collection method was interview. Results: The dimensions of the visible conceptualization of medical knowledge in the metaverse are the concrete effectiveness of the infrastructure elements of medical application patterns as a causal variable, the concrete effectiveness of the facilitator of medical education as a background variable, the concrete effectiveness of the content of medical knowledge as a background variable and the concrete effectiveness of learners' learning as an outcome variable were included in the conceptualization model of knowledge visibility. Conclusion: The visibility of medical knowledge is a process with a collective approach resulting from the cooperation of all elements of educational spaces, which doesn't happen completely without the presence of one element of the process of visibility.